The Company's Legal Compliance Is Limited To The Principles Of Good Corporate Governance In Running A Business - Saputra, Hendrik (Journal of Law, Politic and Humanities, 2025)
This study discusses the legal compliance of Limited Liability Companies (PT) with the principles of Good Corporate Governance (GCG) in the implementation of business activities in Indonesia. One of the important parts of good and sustainable corporate governance is the use of GCG. Law No. 40 of 2007 concerning Limited Liability Companies and Financial Services Authority Regulations are two examples of national laws and regulations that govern the concept of GCG. These include openness, responsibility, accountability, independence, equality, and justice. However, in practice, not all universities are able to implement these principles consistently. This is influenced by various factors, such as weak internal supervision, lack of management commitment, and lack of law enforcement. The consequences of such non-compliance can have serious legal implications, both in the form of civil and criminal liability for management, as well as administrative sanctions from regulators. This study uses a normative juridical approach with a literature study technique to examine the form of legal compliance of universities with GCG and its legal implications. The results of the study show that the consistent implementation of GCG is the main requirement in creating a transparent, accountable, and sustainable business environment. Therefore, it is crucial for Limited Liability Companies to ensure that GCG principles are embedded in every aspect of company management to avoid legal risks and support healthy economic growth.